(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, we focus on the formation of verb adjectives through the substantivization of Turkish nouns using the participle gan. It is known that verb attributes have been studied in Turkology since the 19th century. We focused on the syntactic function of the adjective form formed with the participle - gan. We have provided scientific evidence that morphological features of verbal adjectives are closely related to syntax. In Kyrgyz grammar, the verbal participle is replaced by the verbal adjective, with the verbal adjective becoming an adjectival sentence. Simple sentences are expanded to give an adjectival sentence in the form of a compound sentence. The verb-adjective is in the system of a simple sentence, is an answer to a question, acts as a member of a sentence, and includes the properties of a noun. In modern Kyrgyz, verb-adjectives would be nouns.